Cervical Cerclage in Twin Pregnancies: An Updated Systematic Review and Meta-analysis. Issue 11 (November 2021) - Liu, Yijun; Chen, Meng; Cao, Tiantian; Zeng, Shuai; Chen, Ruixin; Liu, Xinghui
Abstract : (Abstracted from Eur J Obstet Gynecol Reprod Biol 2021;260:137–149) Preventing preterm birth (PTB) in twins is important because the risk is significantly higher compared with singleton pregnancies. The effectiveness of cervical cerclage as an option to prevent PTB in twin pregnancies is unclear.